A Candid Assessment of Standard Cosmology. (1st December 2022) - Melia, Fulvio
Abstract: Modern cosmology is broadly based on the Cosmological principle, which assumes homogeneity and isotropy as its foundational pillars. Thus, there is not much debate about the metric (i.e., Friedmann-Lemaître-Robertson-Walker; FLRW) one should use to describe the cosmic spacetime. But Einstein's equations do not unilaterally constrain the constituents in the cosmic fluid, which directly determine the expansion factor appearing in the metric coefficients. As its name suggests, ΛCDM posits that the energy density is dominated by a blend of dark energy (typically a cosmological constant, Λ), cold dark matter (and a "contamination" of baryonic matter) and radiation. Many would assert that we have now reached the age of "precision" cosmology, in which measurements are made merely to refine the excessively large number of free parameters characterizing its empirical underpinnings. But this mantra glosses over a growing body of embarrassingly significant failings, not just "tension" as is sometimes described, as if to somehow imply that a resolution will eventually be found. In this paper, we take a candid look at some of the most glaring conflicts between the standard model, the observations, and several foundational principles in quantum mechanics, general relativity and particle physics. One cannot avoid the conclusion that the standard model needs a complete overhaul in order to survive.